Plasma ceramides are altered in mild cognitive impairment and predict cognitive decline and hippocampal volume loss - Mielke, Michelle M; Haughey, Norman J; Bandaru, Veera Venkata Ratnam; Schech, Steven; Carrick, Richard; Carlson, Michelle C; Mori, Susumu; Miller, Michael I; Ceritoglu, Can; Brown, Timothy; Albert, Marilyn; Lyketsos, Constantine G (Alzheimer's & dementia, 2010)
A blood-based biomarker of Alzheimer's disease (AD) would be superior to cerebrospinal fluid (CSF) and neuroimaging measures in terms of cost, invasiveness, and feasibility for repeated measures. We previously reported that blood ceramides varied in relation to timing of memory impairment in a population-based study. The present objective was to examine whether plasma ceramides varied by AD severity in a well-characterized clinic sample and were associated with cognitive decline and hippocampal volume loss over 1 year. Participants included 25 normal controls (NC), 17 amnestic Mild Cognitive Impairment (MCI), and 21 early probable AD. A thorough neuropsychological battery and neuroimaging with hippocampal volume determination were conducted at baseline and 1 year later. Plasma ceramides were assayed at baseline using high performance liquid chromatography coupled electrospray ionization tandem mass spectrometry. Although all saturated ceramides were lower in MCI compared with AD at baseline, ceramides C22:0 and C24:0 were significantly lower in the MCI group compared with both NC and AD groups (P < .01). Ceramide levels did not differ (P > .05) in AD versus NC. There were no cross-sectional associations between ceramides C22:0 and C24:0 and either cognitive performance or hippocampal volume among any group. However, among the MCI group, higher baseline ceramide C22:0 and C24:0 levels were predictive of cognitive decline and hippocampal volume loss 1 year later. Results suggest that very long-chain plasma ceramides C22:0 and C24:0 are altered in MCI and predict memory loss and right hippocampal volume loss among subjects with MCI. These plasma ceramides may be early indicators of AD progression.